Real-time and nested polymerase chain reaction in the diagnosis of multifocal serpiginoid choroiditis caused by Mycobacterium tuberculosis - a case report - Shetty, Sachin B (J Ophthalmic Inflamm Infect, 2014)
BACKGROUND: The term multifocal serpiginoid choroiditis (MSC) has been proposed for the infective variant of serpiginous choroiditis (SC) to distinguish it from typical SC believed to be autoimmune related. The role of Mycobacterium tuberculosis (MTb) in MSC has been studied by conventional polymerase chain reaction (PCR). However, the use of real-time PCR (RT-PCR) and nested PCR (N-PCR) in MSC has not been reported. This paper aims to highlight the usefulness of PCR in identifying MTb as a causative agent for MSC leading to its correct treatment with anti-tubercular therapy (ATT). FINDINGS: A young male with a family history of tuberculosis (TB) presented with a history of diminution of vision (DOV) since 3 months in his right eye (RE). He gave similar history in his left eye (LE) since 3 years. His fundus findings were suggestive of MSC. His high-resolution computed tomography (HRCT) chest and Quanti-FERON TB gold results were positive for MTb. These suggested TB to be the likely cause for MSC. This was confirmed by a positive N-PCR report of his aqueous specimen. Further RT-PCR was done to quantify the bacillary load before starting therapy. He was advised 9 months of ATT with 6 weeks of oral steroids. At last follow-up, the RE showed better healing than the LE with fewer chorioretinal scars and a better visual acuity. CONCLUSIONS: RT and N-PCR for MTb are useful in establishing a tuberculous etiology in MSC. Coupled with a good response to ATT, these tests justify the use of ATT in MSC with a PCR-confirmed MTb report. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12348-014-0029-5) contains supplementary material, which is available to authorized users.